ANALISIS NOVEL “PUDARNYA PESONA CLEOPATRA” DAN IMPLIKASINYA TERHADAP KESIAPAN MENIKAH - Zahra, Sabina Kaila; Lestari, Melina; Azizah, Rona; Sabila, Najwaa; Maharani, Annisa; Ashadi, Aurellia Nafish (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This study analyzes the novel "Pudarnya Pesona Cleopatra" by Habiburrahman El Shirazy and its implications for marital readiness. The literature review method was used with primary data sources being the novel and secondary data sources being related articles. The research findings indicate that psychological aspects such as inner conflict and emotional growth of the main character in the novel have significant implications for the readers' readiness for marriage. The data collection method used was content analysis, and the research provides a deeper understanding of the intrinsic elements and moral values contained in the novel. The novel depicts aspects of marital readiness according to Blood of (Rahmawati, 2021a), such as emotional maturity, physical readiness, social maturity, healthy emotions, and role model readiness. Through the novel analysis, it is evident that the main character in the novel demonstrates readiness in these aspects. There are concrete examples in the text that demonstrate aspects of role model readiness, such as responsibility, understanding of the role after marriage, and the ability to perform tasks according to the role, involving the character Raihana in the story